Problems of usual weighted analysis of variance (WANOVA) in randomized block design (RBD) with more than one observations per cell when error variances vary from cell to cell (Bangladesh Journal of Agricultural Research, 2009)
It is well known that classical analysis of variance (ANOVA) is not suitable for heteroscedastic layouts. Weighted analysis of variance (WANOVA) is the only way to deal with such situations. Problems of usual WANOVA in Randomized. Block Design (RBD) with more than one observations per cell with interaction when error variances vary from cell to cell are discussed in this paper. Key Words: Weighted analysis of variance, error variances, cell to cell. DOI: 10.3329/bjar.v34i3.3964 Bangladesh J. Agril. Res. 34(3) : 395-401, September 2009